HUMAN CAPITAL THEORY SEBAGAI LANDASAN TEORITIS DALAM HUMAN RESOURCE DEVELOPMENT - Burhanudin Burhanudin (JURNAL STIE SEMARANG, 2021)
Human resource is an important corporations asset that able to contribute in the achievement of organizational goals and to attain competitive advantages. In order to human resource manageable as the core competencies that is not easily imitated by competitors, the company needs to invest in training and development. The investment in human resource called human capital, and it can be implemented through human resource development (HRD). One of the underlying theories of human resource development is the human capital theory. This paper attempts to provide an overview of the definition of HRD and its components, views on HRD, theoretical foundation of HRD, as well as the human capital theory.